Non-homologous recombination between Alu and LINE-1 repeats results in a 91 kb deletion in MERTK causing severe retinitis pigmentosa - Jonsson, Frida (Mol Vis, 2018)
PURPOSE: Retinitis pigmentosa (RP) represents a large group of inherited retinal diseases characterized by clinical and genetic heterogeneity. Among patients with RP in northern Sweden, we identified two severely affected siblings and aimed to reveal a genetic cause underlying their disease. METHODS: Whole exome sequencing (WES) was performed on both affected individuals. Sequence variants were filtered using a custom pipeline to find a rare or novel variant predicted to affect protein function. Genome-wide genotyping was used to identify copy number variants (CNVs) and homozygous regions with potential disease causative genes. RESULTS: WES uncovered a novel heterozygous variant in the MER proto-oncogene, tyrosine kinase (MERTK) gene, c.2309A>G, p.Glu770Gly located in the tyrosine kinase domain and predicted to be likely pathogenic. The second variant, a large heterozygous deletion encompassing exons 1 to 7 of the MERTK gene, was revealed with genome-wide genotyping. The CNV analysis suggested breakpoints of the deletion, in the 5′-untranslated region and in intron 7. We identified genomic sequences at the site of the deletion as part of L1ME4b (LINE/L1) and AluSx3 that indicated a non-homologous recombination as a mechanism of the deletion evolvement. CONCLUSIONS: Patients with RP in this study were carriers of two novel allelic mutations in the MERTK gene, a missense variant in exon 17 and an approximate 91 kb genomic deletion. Mapping of the deletion breakpoints allowed molecular testing of a cohort of patients with RP with allele-specific PCR. These findings provide additional information about mutations in MERTK for molecular testing of unsolved recessive RP cases and highlight the necessity for analysis of large genomic deletions.